Prevalence of intestinal protozoan parasites among school children in africa: A systematic review and meta-analysis. - Khalid Hajissa; Md Asiful Islam; Abdoulie M Sanyang; Zeehaida Mohamed (Public Library of Science (PLoS), 2022)
Introduction Parasitic infections, especially intestinal protozoan parasites (IPPs) remain a significant public health issue in Africa, where many conditions favour the transmission and children are the primary victims. This systematic review and meta-analysis was carried out with the objective of assessing the prevalence of IPPs among school children in Africa. Methods Relevant studies published between January 2000 and December 2020 were identified by systematic online search on PubMed, Web of Science, Embase and Scopus databases without language restriction. Pooled prevalence was estimated using a random-effects model. Heterogeneity of studies were assessed using Cochrane Q test and I2 test, while publication bias was evaluated using Egger's test. Results Of the 1,645 articles identified through our searches, 46 cross-sectional studies matched our inclusion criteria, reported data from 29,968 school children of Africa. The pooled prevalence of intestinal protozoan parasites amongst African school children was 25.8% (95% CI: 21.2%-30.3%) with E. histolytica/ dispar (13.3%; 95% CI: 10.9%-15.9%) and Giardia spp. (12%; 95% CI: 9.8%-14.3%) were the most predominant pathogenic parasites amongst the study participants. While E. coli was the most common non-pathogenic protozoa (17.1%; 95% CI: 10.9%-23.2%). Conclusions This study revealed a relatively high prevalence of IPPs in school children, especially in northern and western Africa. Thus, poverty reduction, improvement of sanitation and hygiene and attention to preventive control measures will be the key to reducing protozoan parasite transmission.